Microfacies and paleoenvironmental study of Limestone of the Peneta Formation from Kerinci Area - Akmaluddin, Akmaluddin; Nurhidayah, Efrilia Mahdilah; Agustin, Muhammad Virgiawan; Wirakusuma, Fadhil; Novian, Moch. Indra; Barianto, Didit Hadi (Jurnal Kelautan Tropis, 2024)
The research location is the Tebing Tinggi Village, Kerinci region - Jambi, part of the Barisan Zone. This study focuses on the limestone of the Peneta Formation, which is part of the Pre-Tertiary age. The research will investigate the characteristics of carbonate rocks in the Peneta Formation, including the developed facies, fossil content, and the diagenesis process in the Peneta Formation using field data, petrography, and XRD. Our research has succeeded in dividing the Limestone of the Peneta Formation into 3 lithofacies in the study area, including dismicrite, dolomitic limestone, and meta-mudstone. The lack of marine organisms and the dominance of the mudstone facies indicate that the limestone of the Peneta Formation was deposited in an evaporite or brackish zone environment. The limestone diagenesis process was also confirmed in this study. The research location is included in the mesogenesis stage due to the presence of foliation structures, decussate texture, and dolomite minerals until the telogenesis stage, which is characterized by sparite calcite blocky. Furthermore, forsterite and diaspore minerals were also identified through petrographic and XRD analysis, indicating the occurrence of metamorphic processes at our research location.